BIOINFORMATICS STUDY OF 7,8-DIHYDROXYFLAVONE AS A NEUROPROTECTIVE AGENT IN ISCHEMIC STROKE VIA TRKB REGULATION AND GLUTAMINASE INHIBITION - Rislan Faiz Muhammad; Basya Adnani; Safira Dita Arviana; Aldita Husna Violita; Husnul Khotimah; Shahdevi Nandar Kurniawan; Mokhamad Fahmi Rizki Syaban; Yuyun Yueniwati Prabowowati Wadjib; Masruroh Rahayu (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Stroke, particularly ischemic stroke, is one of the leading causes of death worldwide. Ischemic stroke causes a failure of oxidative phosphorylation and ATP synthesis, resulting in high levels of reactive oxygen species (ROS), neuroinflammatory responses, and apoptosis, all of which result in cell death. Neuroprotective agents are given to prevent the infarct area from expanding. Objective: This study aims to predict an in silico interaction by 7,8-dihydroxyflavone as neuprotective agent through TrkB signaling and inhibiting Glutaminase activity. Methods: In silico simulation with 7,8-dihydroxyflavone (DHF) as neuroprotective agent using PubChem, RCSB, Biovia Discovery Studio, PyRx, and PyMol software. This study analyzes the pharmacokinetics, pharmacodynamics, and protein-ligand interactions between 7,8-DHF as a ligand with TrkB (4AT5) and Glutaminase (5JYO) as protein target, compared to their native ligand. Results: 7,8 DHF binds to 4AT5 and 5JYO with lower bond energy (-9.4 Kcal/mol and -6.3 Kcal/mol, respectively) than the native ligand (-5 Kcal/mol and -5.9 Kcal/mol, respectively). It means that 7,8-DHF may increase protective mechanism. Conclusion: These findings tend to increase downstream signaling pathways, leading to increased TrkB expression, which induces protective mechanisms, and decreased glutamate expression, which reduces glutamate toxicity.